Infinite Population Utilitarian Criteria - Geir B. Asheim; Kohei Kamaga; Stéphane Zuber (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine utilitarian criteria for evaluating profiles of wellbeing among infinitely many individuals. Motivated by the non-existence of a natural 1-to-1 correspondence between people when alternatives have different population structures, with a different number of people in each generation, we impose equal treatment in the form of Strong Anonymity. We show how a novel criterion, Strongly Anonymous Utilitarianism, can be characterized by combining Strong Anonymity with other regularity axioms (Monotonicity, Finite Completeness, and continuity axioms) as well as axioms of equity, sensitivity, separability, and population ethics. We relate it to other strongly anonymous utilitarian criteria and demonstrate its applicability by showing how it leads to an efficient and sustainable stream in the Ramsey model.
Keywords: D63; D71; Q01; 330; utilitarianism; intergenerational equity; population ethics